Tannenberg (Grunwald) in der deutschen Tradition des 19. und - Arnold, Udo (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2015)
Tannenberg (Grunwald) in the German tradition of the 19th and 20th centuries Throughout early modern history, the battle of Grunwald, or Tannenberg in German, has served as an important symbol in both Poland and Germany. From the perspective of the latter, for a long time it evoked a sense of shame and defeat that German historiography tried to conceal by confronting it with the heroism of Heinrich von Plauen and the successful defence of Marienburg after the battle. This was the official narrative promoted in German schools. Following the German victory over the Russian Army in Tannenberg in 1914, the site was recast as a positive symbol of German might in the east. The Teutonic defeat of 1410 and the victory of 1914 were presented as part o the same struggle with Russians and Poles who were ascribed the same, pan-Slavic identity. Nonetheless, these efforts were only partially successful as the battle of 1914 was not as famous as other major battles such as Waterloo. After 1945 Tannenberg gradually disappeared from German popular imagination. It was remembered by those expelled from the east as part of their local history but is no longer presented as crucial in Germany history books for schools. Its symbolic value for the German historiography therefore, is largely lost.